Synechocystis: Not Just a Plug-Bug for CO2, but a Green E. coli - Branco dos Santos, Filipe; Du, Wei; Hellingwerf, Klaas J. (Frontiers in Bioengineering and Biotechnology, 2014)
Following multiple reports warning for threats posed by raising levels of atmospheric CO2, it is of paramount importance that human society rapidly evolves to be sustainable. Processes relying on photosynthetic microorganisms, converting CO2 and water into compounds of interest, fuelled by light, are very pertinent, particularly if not directly competing for arable land. Here, we identify specific research questions that remain to be targeted to exploit the full potential of cyanobacterial cell factories. We argue that this approach will be more likely to be successful if organisms such as Synechocystis are not perceived as mere chassis for CO2 fixation, but rather considered as the ‘green’ E. coli.